Can cereal-legume intercrop systems contribute to household nutrition in semi-arid environments: A systematic review and meta-analysis - Chimonyo, Vimbayi Grace Petrova; Govender, Laurencia; Nyathi, Melvin; Scheelbeek, Pauline Franka Denise; Choruma, Dennis Junior; Mustafa, Maysoun; Massawe, Festo; Slotow, Rob; Modi, Albert Thembinkosi; Mabhaudhi, Tafadzwanashe (Frontiers Media, 2023)
Introduction: Intercropping cereals with legumes can intensify rainfed cereal monocropping for improved household food and nutritional security. However, there is scant literature confirming the associated nutritional benefits. Methodology: A systematic review and meta-analysis of nutritional water productivity (NWP) and nutrient contribution (NC) of selected cereal-legume intercrop systems was conducted through literature searches in Scopus, Web of Science and ScienceDirect databases. After the assessment, only nine articles written in English that were field experiments comprising grain cereal and legume intercrop systems were retained. Using the R statistical software (version 3.6.0), paired t-tests were used to determine if differences existed between the intercrop system and the corresponding cereal monocrop for yield (Y), water productivity (WP), NC, and NWP. Results: The intercropped cereal or legume yield was 10 to 35% lower than that for the corresponding monocrop system. In most instances, intercropping cereals with legumes improved NY, NWP, and NC due to their added nutrients. Substantial improvements were observed for calcium (Ca), where NY, NWP, and NC improved by 658, 82, and 256%, respectively. Discussion: Results showed that cereal-legume intercrop systems could improve nutrient yield in water-limited environments. Promoting cereal- legume intercrops that feature nutrient-dense legume component crops could contribute toward addressing the SDGs of Zero Hunger (SDG 3), Good Health and Well-3 (SDG 2) and Responsible consumption and production (SDG 12).